THE EFFORTS OF RELIGIOUS TEACHERS IN OVERCOMING STUDENT'S DELAY MADRASAH TSANAWIYAH BRAJA SAKTI WAY JEPARA - Fresyam Antika Ajeng; Rahmawati (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2021)
Today the world of education is being hit by a very deep concern with the frequent occurrence of student delinquency or what is known as student delinquency which has a serious impact on the development of themselves (students) and society. Because being naughty is an anti-social act, violating applicable law, which is carried out by a person who is approaching adulthood with his own knowledge which, if committed by an adult, is qualified as a crime. News about delinquency is like bullets in the battlefield and the unfortunate thing is that the school is always hit by insults, and it is not uncommon for people to think that the low quality of student behavior or personality is due to the school's inability to control the psyche of its students. Thepurpose of this study was to determine the forms of student delinquency, the factors that influence student delinquency and school efforts in overcoming student delinquency in Madrasah Tsanawiyah Al-Ikhlas Braja Sakti, East Lampung Regency. To obtain accurate data, the authors use qualitative descriptive research, namely by describing methodsand analyze the research results without using the calculation formula, while in obtaining the data the authors use direct observation, interviews with informants, and documentation.